2014
DOI: 10.1111/sltb.12073
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk among Lesbian, Gay, Bisexual, and Transgender Military Personnel and Veterans: What Does the Literature Tell Us?

Abstract: Research suggests that both the military and veteran and the lesbian, gay, bisexual, and transgender (LGBT) populations may be at increased risk for suicide. A literature review was conducted to identify research related to suicide risk in the LGBT military and veteran populations. Despite the paucity of research directly addressing this issue, themes are discussed evident in the literature on LGBT identity and suicide risk as well as LGBT military service members and veterans. Factors such as social support a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 87 publications
2
40
0
Order By: Relevance
“…Results have indicated that homosexuals who perceived discrimination tend to experience higher suicidal ideation. This is consistent with previous findings, indicating alienation and interpersonal rejection due to one's sexual orientation as fuel to suicide vulnerability (Gomez et al, 2011;Hong, Espelage, & Kral, 2011;Matarazzo et al, 2014). The association between perceived discrimination and suicidal ideation may also be explained by the elevation of emotional distress, as these individuals have to deal with stressors related to a stigmatized identity, which is then linked to suicidal ideation (Rosario, Schrimshaw, & Hunter, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results have indicated that homosexuals who perceived discrimination tend to experience higher suicidal ideation. This is consistent with previous findings, indicating alienation and interpersonal rejection due to one's sexual orientation as fuel to suicide vulnerability (Gomez et al, 2011;Hong, Espelage, & Kral, 2011;Matarazzo et al, 2014). The association between perceived discrimination and suicidal ideation may also be explained by the elevation of emotional distress, as these individuals have to deal with stressors related to a stigmatized identity, which is then linked to suicidal ideation (Rosario, Schrimshaw, & Hunter, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Schmitt, Branscombe, Postmes, and Garcia (2014) also pointed to discrimination as the bottom line for the harmful effects on the psychological well-being of homosexuals. This is further supported by different studies describing discrimination as a burden of suicidality among homo-sexuals (Kohlbrenner, Deuba, Karki, & Marrone, 2016;Matarazzo et al, 2014). Among all countries, the United States has the most advanced and well-developed…”
Section: Introductionmentioning
confidence: 68%
“…Nasser and Overholser () found that social support promoted recovery from depression among psychiatric inpatients. Social support was linked with reduced suicide risk in veterans who were identified as lesbian, gay, bisexual, or transgender (Matarazzo et al., ); in individuals diagnosed with mood disorders (Isometsä, ); and in veterans diagnosed with severe mental illness (Montross Thomas et al., ). Further, DeBeer, Kimbrel, Meyer, Gulliver, and Morissette () highlighted the importance of assessing social support in military veterans, as social support reduced the effect of posttraumatic stress disorder (PTSD) and depression symptoms on suicide ideation.…”
mentioning
confidence: 99%
“…For those who wish to serve, have served, or are currently serving, the repeal has the potential to improve quality of life; the secrecy that LGBT soldiers endured under DADT enabled untold amounts of blackmailing, harassment, and sexual violence (Cochran, Balsam, Flentje, Malte, & Simpson, ; Moradi, ; Pelts, Rolbiecki, & Albright, ; Ramirez et al, ) and put LGB personnel and veterans at higher risk for self‐harm and suicide (Matarazzo et al, ). The possibility of open service severely curtails the power of outing threats.…”
Section: The Impact Of Open Service In the Us Militarymentioning
confidence: 99%